Object-oriented database technology for GIS : seminar workbook - 274648 Frank, Andrew; Egenhofer, Max J.; National Center for Gegraphic Information and Analysis; GIS/LIS (1989 : San Antonio, Texas) (Orono, Maine : National Center for Geographic Information & Analysis, 1988)
28